Abnormal Cathodic Photocurrent Generated on an n‐Type FeOOH Nanorod‐Array Photoelectrode. Issue 14 (16th February 2016) - Chen, Hongjun; Lyu, Miaoqiang; Liu, Gang; Wang, Lianzhou
Abstract: A simple, wet‐chemical method for the synthesis of an FeOOH nanorod‐array photoelectrode on fluorine‐doped tin oxide (FTO) glass is reported. Nanorods of diameter about 35 nm and length about 300 nm have been vertically grown on an FTO substrate. Upon calcination, the FeOOH phase could be easily converted to a hematite structure while maintaining the shape of the nanorod array. An interesting abnormal cathodic photocurrent is generated on the FeOOH nanorod‐array photoelectrode under illumination, which is totally different from that obtained on a calcined hematite photoelectrode under the same experimental conditions. The cathodic photocurrent density generated on the FeOOH photoelectrode can also be tuned by applying an electrochemical anodic or cathodic treatment. Detailed analysis has revealed that higher valence state Fe IV species in the FeOOH photoelectrode play an important role in sacrificing the photoexcited electrons for generation of the cathodic photocurrent. Comparison between the FeOOH and hematite photoelectrodes allows for a better understanding of the interplay between crystal structure, surface reactions, and photocurrent. The findings on this new abnormal phenomenon could also provide guidance for the design of new types of semiconducting photoelectrochemical devices. Abstract : Cathodic adventures : An interesting abnormal cathodic photocurrent is generated on an n‐type FeOOH/FTO photoelectrode. In contrast, the calcined hematite/FTO photoelectrode can only generate an anodic photocurrent (see scheme). Through detailed analysis, we surmise that the abnormal cathodic photocurrent may be related to a higher valence Fe IV species, which acts as an effective electron scavenger and thereby contributes to current generation.